A case of craniopagus parasiticus: an antenatal diagnosis by ultrasound screening at 16 weeks of gestation and a literature review of recently reported cases - Houda Nasser Al-Yaqoubi; Nishat Fatema; Badriya Sulaiman Al-Fahdi (The Turkish Journal of Pediatrics, 2019)
Craniopagus parasiticus (CP) is a rare type of malformation of conjoined twins, with one degenerated or underdeveloped parasite twin united at the cranium with the other fully developed twin. Only a handful of cases have been documented in the literature to date. The incidence of this rare deformity is approximately 4 to 6 out of every 10,000,000 live births. We report on a case of CP, diagnosed at 16 weeks of gestation by ultrasound screening. To the best of our knowledge, the case that we present is the first CP case that was diagnosed at such an early gestational age. The formed fetus was found to harbour complex cardiac anomalies. In view of poor prognosis of survival after delivery and upon permission from the couple, the pregnancy was terminated at 17 weeks of gestation.